Hybrid Nanocomposites: Unidirectional High‐Power Generation via Stress‐Induced Dipole Alignment from ZnSnO3 Nanocubes/Polymer Hybrid Piezoelectric Nanogenerator (Adv. Funct. Mater. 1/2014). (January 2014) - Lee, Keun Young; Kim, Dohwan; Lee, Ju‐Hyuck; Kim, Tae Yun; Gupta, Manoj Kumar; Kim, Sang‐Woo
<x xml:space="preserve">Abstract</x> On page 37, S.‐W. Kim and co‐workers report unidirectional high‐power generation from piezoelectric nanogenerators via stress‐induced dipole alignment from single‐crystalline piezoelectric perovskite ZnSnO3 nanocube/polydimethylsiloxane hybrids. This is achieved without applying electrical poling. A recordable large output voltage of about 20 V and an output current density of about 1 μA cm−2 from the device are successfully obtained while rolling under a vehicle tire. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>